Pilot performance comparison between electronic and paper instrument approach charts. (March 2018) - Winter, Scott R.; Milner, Mattie N.; Rice, Stephen; Bush, Dylan; Marte, Daniel A.; Adkins, Evan; Roccasecca, Angela; Rosser, Timothy G.; Tamilselvan, Gajapriya
Highlights: This study compares electronic and paper charts on pilot performance. Participant's had reduced response times using electronic charts. Workload was reported as less when using electronic charts. Observed flight performance was better with electronic charts. Abstract: Electronic flight bags (EFB's) have become common in the era of technologically advanced aircraft (TAA) and glass cockpits. However, many pilots still rely on paper charts as backups in case of electronic failures. The purpose of this study was to examine pilot performance differences when using electronic and paper instrument approach charts. Twenty-nine participants from a large university completed the study in a fixed-based flight-training device (FTD). While completing a flight between two major cities, the participants were asked to answer questions on instrument approach charts using an electronic flight bag. Halfway through the questions, the electronic flight bag was said to have failed, and participants were provided with paper charts. The findings indicate that participants' response time was significantly lower using electronic charts over paper ones. Flight performance, as observed via video footage, indicated far worse control of altitude and course when using paper charts than when electronic charts were used. In a post-test instrument, participants' poorly estimated the their average response time to questions in both conditions. Finally, participants' indicated that they felt the use of electronic charts reduced their workload as measured by the NASA TLX. The paper discusses the practical applications of these findings.